2018
DOI: 10.1073/pnas.1720798115
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary genomic dynamics of Peruvians before, during, and after the Inca Empire

Abstract: SignificanceThrough the Peruvian Genome Project we generate and analyze the genomes of 280 individuals where the majority have >90% Native American ancestry and explore questions at the interface of evolutionary genetics, history, anthropology, and medicine. This is the most extensive sampling of high-coverage Native American and mestizo whole genomes to date. We estimate an initial peopling of Peru was rapid and began by 12,000 y ago. In addition, the mestizo populations exhibit admixture between Native Ameri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
154
2
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(180 citation statements)
references
References 88 publications
13
154
2
11
Order By: Relevance
“…2A, CO/MO cluster), also contained patients with high IA ancestry. This observation is in line with previously described IA population migration patterns and genetic admixture in Peru (38). A small number of individuals in the study were identified who had high proportion of Asian or African ancestry (>50%), each group accounting for approximately 0.5% of the patients.…”
Section: Distribution Of Genetic Ancestrysupporting
confidence: 90%
“…2A, CO/MO cluster), also contained patients with high IA ancestry. This observation is in line with previously described IA population migration patterns and genetic admixture in Peru (38). A small number of individuals in the study were identified who had high proportion of Asian or African ancestry (>50%), each group accounting for approximately 0.5% of the patients.…”
Section: Distribution Of Genetic Ancestrysupporting
confidence: 90%
“…Genome-wide data from contemporary populations suggested a single expansion wave into South America with little gene flow between groups (4) [but see (36)]. By contrast, analysis of later Holocene genomes suggests that South Americans derived from one or more admixture events between two ancestral NA groups, possibly via multiple movements into South America (7).…”
Section: Multiple Dispersals Into South Americamentioning
confidence: 99%
“…A recent publication about GCK-MODY in the US National Monogenic Diabetes Registry, shows that the majority of Registry participants with a GCK-MODY phenotype selfidentified as Caucasian and there was underrepresentation of a number of ethnic minorities when compared to the greater US population and ethnicity-specific diabetes rates [5]. This is the first reported case in Perú, and in a Mestizo-Peruvian ethnic group, which consist in a population with Native-American and European ancestries [13]. Other countries in Latin America, such as Argentina and Chile, also have reported cases mainly associated with GCK-MODY, which seems to be frequent in our region [6,7,14].…”
Section: Discussionmentioning
confidence: 80%